(untitled) (Global Journal of Human-Social Science, 2019)
Allen Ginsberg, one of the most rebellious poets in the history of American literature, throughout his life as a poet had taken poetry as a form of protest against different issues. These issues range from conventional societal norms, their justification instead of being suppressive and detrimental to the development of one’s true self, to the hypocritical and arbitrary role of the contemporary American government. This paper aims to show how Ginsberg’s poetry unmasks the true nature of all the oppressive operations of society and authority. Through the historical background and analysis of three of his poems, this paper also aims at showing the ways Ginsberg used poetry as a form of protest and rebellion against those operations that emphasize the arbitrary interest of the capitalistic society over individual selves, even at the cost of destroying them completely.